2022
DOI: 10.3390/biomedicines10061277
|View full text |Cite
|
Sign up to set email alerts
|

Effective Radiosensitization of Bladder Cancer Cells by Pharmacological Inhibition of DNA-PK and ATR

Abstract: This study aims at analyzing the impact of the pharmacological inhibition of DNA damage response (DDR) targets (DNA-PK and ATR) on radiosensitization of bladder cancer cell lines of different molecular/histological subtypes. Applying DNA-PK (AZD7648) and ATR (Ceralasertib) inhibitors on SCaBER, J82 and VMCUB-1 bladder cancer cell lines, we revealed sensitization upon ionizing radiation (IR), i.e., the IC50 for each drug shifted to a lower drug concentration with increased IR doses. In line with this, drug expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Colony formation was determined as previously described [ 35 ] with slight modifications: Cells were plated into six‐well plates (EJ28: 75 × 10 2 cells per well; SCaBER: 1 × 10 3 cells per well; J82: 1 × 10 3 cells per well) in triplicate and cultured in growth medium with G418 for 10 days. After cultivation (37 °C, 5% CO 2 ), the colonies were stained in 0.05% crystal violet solution (10% formaldehyde, 80% methanol).…”
Section: Methodsmentioning
confidence: 99%
“…Colony formation was determined as previously described [ 35 ] with slight modifications: Cells were plated into six‐well plates (EJ28: 75 × 10 2 cells per well; SCaBER: 1 × 10 3 cells per well; J82: 1 × 10 3 cells per well) in triplicate and cultured in growth medium with G418 for 10 days. After cultivation (37 °C, 5% CO 2 ), the colonies were stained in 0.05% crystal violet solution (10% formaldehyde, 80% methanol).…”
Section: Methodsmentioning
confidence: 99%
“…These kinds of inhibitors were shown to be effective, especially in the treatment of head and neck squamous cell carcinoma, in combination with other therapies such as surgery, RT, and chemotherapy [176]. They also specifically target DDR pathways and impair DSB repair processes, exhibiting significant radiosensitizing effects [177]. CHK1 is also related to as many as thirty-eight compounds, according to DrugBank, the majority of which are investigational or experimental.…”
Section: Targeting Essential Phosphorylation Factors For Regulating Ddrmentioning
confidence: 99%
“…In mammals, c-NHEJ is the main repair pathway for DSB processing and operates with fast kinetics and efficiency, throughout the cell cycle [ 42 , 139 , 140 , 141 ]. Inhibition of c-NHEJ is shown to confer marked radiosensitivity in a wide range of cells [ 142 , 143 , 144 ]. We recently reported that at low doses of IR, c-NHEJ is partly suppressed by mechanisms that remain to be characterized, giving thus way to HR [ 131 , 145 , 146 ].…”
Section: Shift Of Balance To Error-prone Dsb Repair Pathways Is Likel...mentioning
confidence: 99%